Smartphone apps - Düking, P.; Sperlich, B. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
The use of smartphones and smartphone applications (apps) is steadily increasing. The sensor technologies installed, and the algorithms applied offer the possibility to record various sports-related parameters. This allows to quantify performance and health parameters in real-life scenarios on a large number of individuals. The smartphone camera (high-speed camera) can e.g. collect biomechanical running parameters such as ground contact time. Likewise, the built-in camera technology allows to capture movement velocity during strength training to control training processes according to the concept of "velocity-based training". Smartphone apps can support the control of training processes in endurance sports by simplifying the recording, analysis, and interpretation of heart rate variability.